Association between sedentary time and metabolic syndrome: A cross-sectional study among Chinese Garze Tibetans - Guo, Lei; Liu, Yixuan; Xue, Tingting; Liang, Liang; Nima, Yongcuo; Yang, Yang; Li, Qun; Zhang, Qiushi (Frontiers in Public Health, 2022)
Abstract Background Chinese Tibetans have long hours of sitting without much physical activity given their religious behavior, resulting in potential harmful health hazards. However, the relationship between sedentary time and metabolic syndrome (MetS) has not been investigated in Chinese Tibetans. Methods From Jan 2021 to Jun 2022, residents in Garze Tibetan Autonomous Prefecture in Southwest China’s Sichuan province were recruited using a multi-stage, stratified, random-cluster sampling strategy. MetS were ascertained using definition proposed by the International Diabetes Federation. Associations between sedentary time and the prevalence of MetS in the total sample and by age and sex were estimated using logistic regression models. Results Among 971 Chinese Tibetan participants (mean age 41.1 years and 73.8% female), 319 (32.9%) were diagnosed as having MetS. We found positive associations of sedentary time over 11 hours per day with the prevalence of MetS in crude (OR: 1.23; 95% CI: 1.12 to 1.36, p-value <0.001), age and sex adjusted (OR: 1.18; 95% CI: 1.08 to 1.29, p-value <0.001), and fully adjusted (OR: 1.17; 95% CI: 1.08 to 1.29, p-value <0.001) models, compared to those who had less than eight hours of sedentary time per day. Sensitivity analyses suggest consistent positive association between sedentary time and each metric of MetS. Conclusions Sedentary time longer than 11 hours per day is significantly associated with increased risk of MetS, suggesting that polices to advocate health education may alleviate the health burden of MetS among Tibetans in China.